Variety of Flavors, Appropriate Technology, and Online Marketing for Developing Milkfish Cracker Small Business - Zainal Abidin Achmad; Didiek Tranggono; Sri Tjondro Winarno; Sonja Andarini; Kusuma Wardhani Mas’udah (Plakat : Jurnal Pelayanan Kepada Masyarakat, 2022)
This community service activity aims to increase the income of the milkfish cracker home industry by fisherwomen in Kalanganyar Village, Sedati District, Sidoarjo Regency. The method of implementing the activity uses counseling sessions, training, and practice. The counseling materials are (1) the importance of developing a variety of quality crackers to increase sales volume, (2) the importance of making attractive and hygienic packaging for marketing milkfish cracker products. At the same time, the training material is making hygienic cracker dough with variations in original and spicy flavors. The application of appropriate technology was an electric machine for cutting cylindrical cracker dough. While the online marketing tool developed is Instagram. The conclusions of this activity are (1) training in making hygienic cracker dough with a variety of flavors, (2) improving marketing channel strategies, (3) redesigning product brands, (4) increasing production capacity.